CRAN-27. PAEDIATRIC EXTRAVENTRICULAR NEUROCYTOMA: A SERIES AND A RARE COMPLICATION. Issue 2 (22nd June 2018) - Johnson, Alexandra; Bye, Annie; Ziegler, David; Gifford, Andrew; Jacobsen, Erica; Cohn, Richard
Abstract: Paediatric extraventricular neurocytoma (EVN) is a rare central nervous system (CNS) tumour accounting for 0.1% of CNS tumours (Liu et al 2013). Limited data exists regarding presentation and outcome of paediatric EVN. A retrospective review of patients presenting with EVN to Sydney Children's Hospital was conducted between 2007 and 2015 inclusively. Demographic data, presenting symptoms, seizure type and post-surgical outcome were examined. Four patients presented with EVN. Age at presentation ranged between 6–15 years (median 9.75), with follow-up of 2–10 years (median 6.6). Presenting features included focal seizures (n=2), generalised seizures (n=1) and headache (n=2). Two patients had focal neurological signs, one with homonymous hemianopia and another with sudden decline including dysarthria, hemiparesis and ipsilateral facial palsy accompanied by impaired consciousness. This latter patient had an intratumoral haemorrhage, cerebral oedema and enhancement of tumour periphery on magnetic resonance imaging / angiogram (MRI/MRA). MRA showed tortuous branching vessels from middle cerebral artery and AV shunting in the tumour bed. All patients had a gross total resection, and histopathology showed Ki67 <2% in all, though microvascular proliferation was noted (n=2, including the patient with haemorrhage). Recurrence including cerebellar metastasis and localised nodules occurred in the patient with haemorrhage. Focal seizures developed 4 years post-operatively, responding to carbamazepine. All other patients remained seizure free without recurrence post-operatively. Haemorrhage is a rare finding in EVN with 6 adults previously reported, including one with sudden hemiparesis (Ritz et al 2005). Clinicians should be aware of rare dramatic presentations in EVN due to intratumoral haemorrhage.